Engineered biomimetic nanovesicles show intrinsic anti-inflammatory properties for the treatment of inflammatory bowel diseases. Issue 38 (21st September 2017) - Corbo, Claudia; Cromer, Walter E.; Molinaro, Roberto; Toledano Furman, Naama E.; Hartman, Kelly A.; De Rosa, Enrica; Boada, Christian; Wang, Xin; Zawieja, David C.; Agostini, Marco; Salvatore, Francesco; Abraham, Bincy P.; et al.
Abstract : We debut for the first time specialized leukosomes (SLKs) for the treatment of inflammatory bowel disease. Abstract : Inflammatory bowel disease (IBD), which includes Crohn's disease and ulcerative colitis, is a chronic inflammatory condition of the gastrointestinal (GI) tract. Currently, it is treated with immunosuppressant or biologics that often induce severe adverse effects. Thus, there is an urgent clinical need for more specific treatments. To provide a valid therapeutic tool for IBD therapy, in this work we developed biomimetic nanovesicles by manipulating leukocyte membranes to exploit mechanisms of T-cell recruitment during inflammation. A subset of T-lymphocytes participates in homing to inflamed tissue in the gastrointestinal tract by overexpressing the α4β7 integrin, which is responsible for binding to its receptor on the endothelial membrane, the mucosal addressin cell adhesion molecule 1. Based on this principle, we engineered biomimetic vesicles, referred to as specialized leukosomes (SLKs), which are leukocyte-like carriers 'doped' with the α4β7 integrin over-induced in purified immune cells. We tested SLKs in an in vivo murine model of IBD induced by treatment with dextran sulfate sodium. Notably, treatment of IBD mice with SLKs allowed us to observe a reduction of inflammation (favorable modulation of both pro- and anti-inflammatory genes, as well as reduction of immune cells infiltration into the colon tissue), and a consequent enhanced intestinal repair (low epithelial damage). In this study, we demonstrate that biological-derived nanoparticles can be used not only as naturally targeted drug delivery systems, but also as nano-therapeutics endowed with intrinsic anti-inflammatory properties.